NIMG-62. 68(GA)DOTATATE PET-BASED RADIATION CONTOURING CREATES SMALLER AND MORE PRECISE RADIATION VOLUMES FOR MENINGIOMA PATIENTS. (12th November 2021) - Perlow, Haley; Yang, Michael; Siedow, Michael; Gokun, Yevgeniya; McElroy, Joseph; Matsui, Jennifer; Beyer, Sasha; Arnett, Andrea; Boulter, Daniel; Fritz, Joel; Miller, Eric; Blakaj, Dukagjin; et al.
Abstract: PURPOSE: Radiation treatment planning for meningiomas conventionally involves MRI contrast enhanced images to define residual tumor. However, the gross tumor volume may be difficult to delineate for patients with a meningioma in the skull base, sagittal sinus, or post resection. Advanced PET imaging using 68(GA)DOTATATE PET, which has been shown to be more sensitive and specific than MRI imaging, can be used for target volume delineation in these circumstances. We hypothesize that 68(GA)DOTATATE PET scan-based treatment planning will lead to smaller radiation volumes and will detect additional areas of disease compared to standard MRI alone. METHODS: Our data evaluated retrospective, deidentified, and blinded gross tumor volume (GTV) contour delineation with 7 CNS specialists (3 neuroradiologists, 4 CNS radiation oncologists) for 26 patients diagnosed with a meningioma who received both a 68(GA)DOTATATE PET and an MRI for radiation treatment planning. Both the MRI and the PET were non-sequentially contoured by each physician for each patient. RESULTS: The mean MRI volume for each physician ranged from 24.14-35.52 ccs. The mean PET volume for each physician ranged from 10.59-20.54 ccs. The PET volumes were significantly smaller for 6 out of the 7 physicians. In addition, 7/26 (27%) patients had new non-adjacent areas contoured on PET by at least 6 of the 7 physicians that were not contoured by these physicians on the corresponding MRI. These new areas would not have been in the traditional MRI based volumes. CONCLUSION: Our study supports that 68(GA)DOTATATE PET imaging can help radiation oncologist create smaller and more precise radiation treatment volumes. Utilization of 68(GA)DOTATATE PET may find undetected areas of disease which in turn can improve local control and progression free survival. 68(GA)DOTATATE PET guided treatment planning should be studied prospectively.